Expression profiling of Echinococcus multilocularis miRNAs throughout metacestode development in vitro. - Natalia Macchiaroli; Matías Preza; Matías Gastón Pérez; Laura Kamenetzky; Marcela Cucher; Uriel Koziol; Estela Castillo; Matthew Berriman; Klaus Brehm; Mara Cecilia Rosenzvit (Public Library of Science (PLoS), 2021)
The neglected zoonotic disease alveolar echinococcosis (AE) is caused by the metacestode stage of the tapeworm parasite Echinococcus multilocularis. MicroRNAs (miRNAs) are small non-coding RNAs with a major role in regulating gene expression in key biological processes. We analyzed the expression profile of E. multilocularis miRNAs throughout metacestode development in vitro, determined the spatial expression of miR-71 in metacestodes cultured in vitro and predicted miRNA targets. Small cDNA libraries from different samples of E. multilocularis were sequenced. We confirmed the expression of 37 miRNAs in E. multilocularis being some of them absent in the host, such as miR-71. We found a few miRNAs highly expressed in all life cycle stages and conditions analyzed, whereas most miRNAs showed very low expression. The most expressed miRNAs were miR-71, miR-9, let-7, miR-10, miR-4989 and miR-1. The high expression of these miRNAs was conserved in other tapeworms, suggesting essential roles in development, survival, or host-parasite interaction. We found highly regulated miRNAs during the different transitions or cultured conditions analyzed, which might suggest a role in the regulation of developmental timing, host-parasite interaction, and/or in maintaining the unique developmental features of each developmental stage or condition. We determined that miR-71 is expressed in germinative cells and in other cell types of the germinal layer in E. multilocularis metacestodes cultured in vitro. MiRNA target prediction of the most highly expressed miRNAs and in silico functional analysis suggested conserved and essential roles for these miRNAs in parasite biology. We found relevant targets potentially involved in development, cell growth and death, lifespan regulation, transcription, signal transduction and cell motility. The evolutionary conservation and expression analyses of E. multilocularis miRNAs throughout metacestode development along with the in silico functional analyses of their predicted targets might help to identify selective therapeutic targets for treatment and control of AE.